Operation control system of sterilization installation on the basis of the accelerator UELV-10-10-S-70 - Bystrov, P.A.; Pavlov, Yu.S.; Kazyakin, А.А.; Kozlov, A.А. (Вопросы атомной науки и техники, 2019)
The design of the system for monitoring and recording the operating parameters of the radiation installation at the IPCE RAS on the basis of the accelerator UELV-10-10-S-70 is presented. Solutions are proposed for collecting data from the equipment of the sterilization installation and the accelerator, their primary analysis, transfer to the computer for further processing and fixation in the journal. Presented software of the control device. The created device allows you to timely identify and prevent the occurrence of emergency situations.